(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This article analyses the female protagonists of Sashi Deshpande and their struggle to assert theiridentity in society. As part of this particular study, all her novels have been considered, but mostof the analysis focuses on 4 of her major novels, namely Darkness Holds No Terror, Roots and aShadows, That Long Silence and The Vinna Lega. Therefore, in thisaparticular article, an attemt is made to study the female protagonists of Shashi Deshpande as portrayed by her, with a view to recognizing and appreciating their sufferings and trials under the conflicting influence of modernity and tradition.